(untitled) (Revista Electrónica Calidad en la Educación Superior, 2020)
This article shows conceptual approaches to the curriculum and curriculum internationalization, taking into account current strategies such as the use of new technologies for higher education. Likewise, the results of interviews with teachers of the Bachelor of Childhood Education on how to implement the internationalization process from the classroom are presented. The most important results are: teachers cooperate with peers abroad promoting strategies such as classes with universities from abroad through virtual platforms, videoconferences, virtual exchanges and international references in the classes. Blogs, international bibliography, as well as international databases are also used. Regarding intercultural competence, it is also promoted through the inclusion of national intercultural references, such as indigenous people and their culture.